ANOMALIES OF HYOID BONE AND THYROID CARTILAGE: A RARE CASE REPORT - Shetty, Ashok Kumar; Hargi, Gopal G; M G, Pushpa; Gurudut, K S (Journal of Forensic Medicine and Toxicology, 2015)
Anomalies of hyoid bone and thyroid cartilage are a feature very rarely encountered in the clinical set up. But in cases of death due to compression of neck they become a crucial criteria to exactly decide and opine about the manner of death. Congenital anomalies of hyoid bone and thyroid cartilage though are a rare entity, when present can be a herculean task for the forensic expert to identify and opine, and not be biased with respect to the manner of death. Hereby presenting a rare case of such entity.